Exploring the New Social Studies Curriculum at the Third Cycle of Basic Education: Interviews with Curriculum Planners in Erbil Sulaymaniyah and Duhok in Iraq - Qolamani, Khalid Ilias Basheer; Kaya, Erol (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2024)
This study examines the new social studies curriculum in Iraq's basic education system,specifically in Erbil, Sulaymaniyah and Duhok. The reform, informed by constructivistlearning and critical pedagogy, integrates subjects like history and geography to promotecivic responsibility and global awareness. The study, based on interviews with curriculumplanners, explores the motivations and theoretical underpinnings of this reform. It alsoaddresses the practical challenges of implementation, such as resource allocation, teachertraining and cultural adaptations. The curriculum aims to foster critical thinking andinclusivity, balancing global perspectives with local contexts. Challenges highlightedinclude financial constraints and logistical issues in dealing with sensitive topics. Thisstudy underscores the importance of continuous improvement, stakeholder collaborationand adaptive strategies in educational transformation.